Doença do Enxerto-Contra-Hospedeiro genital pós transplante alogênico de medula óssea: prevalência e repercussões ginecológicas - Araújo, Luiza Amorim de Carvalho (2024)
Allogeneic bone marrow transplantation (BMT) carries the risk of the donor's cells recognizing the recipient as abnormal, triggering Graft Versus Host Disease (GVHD). This study aimed to understand the prevalence, gynecological complications and repercussions on sexual function of this disease. To this end, a descriptive cross-sectional study was carried out in which post-allogeneic BMT patients were evaluated and underwent gynecological evaluation. A total of 22 patients between 21 and 61 years old (average 38 years old), with an average of 1028 (± 979) days post BMT were evaluated at the Assis Chateubriand Maternity School. Of these patients, whether or not they had Vulvar and Vaginal Graft Versus Host Disease (GVHD), 15 reported various gynecological complaints (dryness, burning and dyspareunia being the most common) with important repercussions on their sexual function, assessed through the Index of Female Sexual Function. Of the total, twelve showed signs of genital atrophy on examination. A 45% prevalence of GVHDV was found, with vulvar and vaginal involvement of 100 and 60%, respectively. Burning and dyspareunia symptoms were more prevalent in patients with GVHD than in those without it (p<0.05); there was no difference in lesions induced by Human Papillomavirus (HPV) between the two groups. However, compared to the population not undergoing allogeneic BMT, these patients had a higher prevalence of induced HPV lesions and intermediate vaginal flora, assessed by the Nugent score. It is concluded that GVHD is a potentially mutilating condition, with a significant prevalence among post-BMT patients. Genital involvement goes beyond GVHD lesions and this group of patients requires specialized and structured gynecological care.